2019
DOI: 10.1002/smj.3088
|View full text |Cite
|
Sign up to set email alerts
|

Political ideology of the board and CEO dismissal following financial misconduct

Abstract: Research Summary: Why do some boards refuse to take serious action against CEOs who have committed financial misconduct? Past work has directed attention to the antecedents of misconduct while largely overlooking this ques-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 71 publications
2
38
2
Order By: Relevance
“…In general, these different aspects of performance tend to be negatively associated with CEO dismissal, although the precise effects vary to some extent across studies 3 . Additional research has shown that financial misconduct increases CEO dismissal (Park, Boeker, & Gomulya, 2020) and that different characteristics of the CEO (e.g., tenure, social status, firm‐specific knowledge) (Flickinger et al, 2016; Shen & Cannella, 2002a; Wang et al, 2017) as well as board characteristics (e.g., outsider directors, board political ideology, CEO overpayment) (Park et al, 2020; Shen & Cannella, 2002a; Wowak et al, 2011) can also influence dismissal, or alter a CEO's likelihood of being dismissed for poor performance or misconduct.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these different aspects of performance tend to be negatively associated with CEO dismissal, although the precise effects vary to some extent across studies 3 . Additional research has shown that financial misconduct increases CEO dismissal (Park, Boeker, & Gomulya, 2020) and that different characteristics of the CEO (e.g., tenure, social status, firm‐specific knowledge) (Flickinger et al, 2016; Shen & Cannella, 2002a; Wang et al, 2017) as well as board characteristics (e.g., outsider directors, board political ideology, CEO overpayment) (Park et al, 2020; Shen & Cannella, 2002a; Wowak et al, 2011) can also influence dismissal, or alter a CEO's likelihood of being dismissed for poor performance or misconduct.…”
Section: Previous Researchmentioning
confidence: 99%
“…Still, as illustrated in Table 1, there has been variance in how scholars have applied these methods across studies. While many (i.e., about 56%) have used both positive and negative indicators of dismissal (e.g., Hubbard, Christensen, & Graffin, 2017; Park et al, 2020; Wang et al, 2017), some have exclusively focused on one or the other type of indicator (e.g., Dwivedi et al, 2018; Gomulya & Mishina, 2017; Worrell et al, 1993; Wowak et al, 2011; Zorn, DeGhetto, Ketchen, & Combs, 2020). Moreover, specific indicators vary between studies, at least in how they are described.…”
Section: Previous Researchmentioning
confidence: 99%
“…Vicarious learning based on sharing tacit knowledge, for example, through mentoring or apprenticeship, is outside the scope of this paper (e.g., Leonard and Sensiper 1998). 3 We may still observe the influence of ideological heterogeneity within capitalism (e.g., Park et al 2020). 4 The importance of communication is also emphasized by related literature on the attention-based view of the firm (Ocasio 1997), absorptive capacity (Cohen and Levinthal 1990), and knowledge transfer (Szulanski 1996).…”
Section: Discussionmentioning
confidence: 88%
“…Instead of treating capitalism or socialism as singular ideologies, future research could investigate its variants, such as libertarian capitalism, welfare-state capitalism, and conscious capitalism, as the ideological foundation of vicarious learning (cf. Park et al 2020) and organizational practices more generally. It would be also interesting to study political ideologies within capitalism and their effects on organizational learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation